Heterodera schachtii Tyrosinase-like protein - a novel nematode effector modulating plant hormone homeostasis - Habash, Samer S; Radakovic, Zoran S; Vankova, Radomira; Siddique, Shahid; Dobrev, Petre; Gleason, Cynthia; Grundler, Florian M W; Elashry, Abdelnaser (Scientific reports, 2017)
The beet cyst nematode Heterodera schachtii causes major yield losses in sugar beet. Understanding the interaction between H. schachtii and its host plant is important for developing a sustainable management system. Nematode effectors play a crucial role in initializing and sustaining successful parasitism. In our study, we identified a gene (Hs-Tyr) encoding a tyrosinase functional domain (PF00264). We describe Hs-Tyr as a novel nematode effector. Hs-Tyr is localized in the nematode esophageal gland. Up-regulation of its expression coincided with the parasitic developmental stages of the nematode. Silencing Hs-Tyr by RNA interference made the treated nematodes less virulent. When RNAi-treated nematodes succeeded in infecting the plant, developing females and their associated syncytial nurse cells were significantly smaller than in control plants. Ectopically expressing the Hs-Tyr effector in Arabidopsis increased plant susceptibility to H. schachtii, but not to the root-knot nematode Meloidogyne incognita. Interestingly, Hs-Tyr in the plant promoted plant growth and changed the root architecture. Additionally, the expression of Hs-Tyr in Arabidopsis caused changes in the homeostasis of several plant hormones especially auxin and the ethylene precursor aminocyclopropane-carboxylic acid.
Keywords: proteiny červů; hlístice; Esophagus; ezofágus; Nematoda; Host-Parasite Interactions; Arabidopsis; interakce hostitele a parazita; virulence; tyrosinasa; regulátory růstu rostlin; Monophenol Monooxygenase; Virulence; Helminth Proteins; Animals; Plant Growth Regulators; ženské pohlaví; zvířata; Female